Édito - Groupe « Classe inversée » du réseau Reseida (Nantes Université, 2022)
This dossier investigates the so-called flipped classroom, which a growing number of teachers are claiming to be their own. In its best-known or recognised forms, the flipped classroom consists of an interpolation of the traditional division of school work between the inside and outside of the classroom. In practice, teachers who declare to practice this innovation implement it in a wide variety of ways. The authors of the articles consider this variety not as a limitation but as an opportunity for research. This is why they chose not to start from an a priori definition of this polymorphous innovation, but from what teachers say about it, in different disciplines and contexts. The aim is to understand what different elements of the traditional school form teachers choose to shake, why and how they do so. And to analyse, on the one hand, the feedback effects for the students in terms of their learning and the scaffoldings that makes it possible; on the other hand, the feedback effects for the teachers themselves, in terms of their professional development.